The contribution of environmental auditing to achieving the environmental sustainability of industrial enterprises -Dolphin Energy limited model- - benchehida, Fadhila (Journal of Research in Finance and Accounting, 2021)
Environmental sustainability has become the concern of many countries in general and industrial institutions in particular as a result of fear of environmental degradation due to the remnants of industrial activity, which may limit the capabilities of individuals in the future. Therefore, institutions sought to enhance the contribution of environnemental auditing as one of the requirements of an effective environmental management system. This study aims to find out the extent of the contribution of environmental auditing to achieving environmental sustainability, and considering that industrial institutions are the largest institutions that affect the environment from industrial waste and global warming ... etc., so we relied in our study on industrial enterprises and the Dolphin Energy Limited model. Through analyzing the various disclosures related to the environmental aspect of the company, we prepared environmental audit reports, and most of the reports were positive, except for the environmental management system report. It was a conservative report because the company did not obtain ISO 14001 certification.